STUDIES ON LONG WING TRAWL FOR SHRIMPS Off KAKINADA (A. P.) COAST~ (i) RESULTS OF COMPARATIVE FISHING EXPERIMENTS WITH THE CONVENTIONAL TWO SEAM TRAWL - SATYANARAYANA, A V.V; NARAYANAPPA, G; DAWSON, PERCY (Fishery Technology, 2017)
Comparative fishing operations with the conventional twoseam net and a 29.26 m. long wing shrimp trawl of fourseam type were undertaken. The result showed that the fourseam net gave nearly twice prawn catch than that of theconventional type. It was also found that the four seam netcan be developed into a combination trawl for the effectiveexploitation of both prawns and fish along the coasts offKakinada.